2014
DOI: 10.2147/ott.s51664
|View full text |Cite
|
Sign up to set email alerts
|

Renal malignant solitary fibrous tumor with single lymph node involvement: report of unusual metastasis and review of the literature

Abstract: Solitary fibrous tumors are rare mesenchymal spindle cell neoplasms that are usually found in the pleura. The kidneys are an uncommon site and only few cases of renal solitary fibrous tumor exhibit malignant behavior metastasizing to the liver, lung, and bone through the hematogenous pathway.PurposeTo describe the first case of lymph node metastasis from renal solitary fibrous tumor in order to increase the knowledge about the malignant behavior of these tumors.Patients and methodsA 19-year-old female patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…AS unusually harbours from the kidney, and it was first described by Prince in 1942 [18], after a clear definition of this heterogeneous group of the tumour was set [19, 20]. Numerous overlapping radiological characteristics could be observed in particular with RCC [14, 21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…AS unusually harbours from the kidney, and it was first described by Prince in 1942 [18], after a clear definition of this heterogeneous group of the tumour was set [19, 20]. Numerous overlapping radiological characteristics could be observed in particular with RCC [14, 21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is reasonable to treat all SFTs under the assumption that they are highly invasive. Mearini et al [ 14 ] reported a patient with a renal SFT that was difficult to diagnose definitively during the surgery; therefore, lymphadenectomy was performed after which lymph node metastases were discovered after the operation. A 64-year-old patient underwent mass resection, hysterectomy, bilateral salpingo-oophorectomy, and supplementary surgery involving inguinal lymph node dissection for malignant vulval SFT; however, she died of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…SFT in the kidney is mostly benign but has malignant potential. Recently, there has been an increase in the number of reports of malignant SFT, including metastasis to lymph nodes [ 12 ], lung [ 10 , 13 , 14 ], liver [ 13 , 14 ], pancreas [ 11 ] and bone [ 15 , 16 ], local recurrence [ 17 , 3 ], peritoneal implantation [ 3 ], and invasion to renal vein [ 18 ]. Microscopically, the diagnostic criteria for malignant SFT is the presence of increased cellularity with crowded and overlapping nuclei, pleomorphism, necrosis and hemorrhage, increased mitotic activity more than four mitoses per ten high power fields (HPFs) [ 19 , 8 , 7 ].…”
Section: Introductionmentioning
confidence: 99%